Protecting Offspring Against Fire: Lessons From Banksia Seed Pods - Huss, Jessica C.; Fratzl, Peter; Dunlop, John W. C.; Merritt, David J.; Miller, Ben P.; Eder, Michaela (Frontiers in Plant Science, 2019)
Wildfires are a natural component in many terrestrial ecosystems and often play a crucial role in maintaining biodiversity, particularly in the fire-prone regions of Australia. A prime example of plants that are able to persist in these regions is the genus Banksia. Most Banksia species that occur in fire-prone regions produce woody seed pods (follicles), which open during or soon after fire to release seeds into the post-fire environment. For population persistence, many Banksia species depend on recruitment from these canopy-stored seeds. Therefore, it is critical that their seeds are protected from heat and rapid oxidation during fire. Here, we show how different species of Banksia protect their seeds inside follicles while simultaneously opening up when experiencing fire. The ability of the follicles to protect seeds from heat is demonstrated by intense 180 second experimental burns, in which the maximum temperatures near the seeds ranged from ~75 °C for B. serrata to ~90 °C for B. prionotes and ~95 °C for B. candolleana, contrasting with the mean surface temperature of ~450 °C. Many seeds of native Australian plants, including those of Banksia, are able to survive these temperatures. Structural analysis of individual follicles from these three Banksia species demonstrates that all of them rely on a multicomponent system, consisting of two valves, a porous separator and a thin layer of air surrounding the seeds. The particular geometric arrangement of these components determines the rate of heat transfer more than the tissue properties alone, revealing that a strong embedment into the central rachis can compensate for thin follicle valves. Furthermore, we highlight the role of the separator as an important thermal insulator. Our study suggests that the genus Banksia employs a variety of combinations in terms of follicle size, valve thickness, composition and geometric arrangement to effectively protect canopy-stored seeds during fire.